Some Notes on Terborgh's "The Bogey of Economic Maturity" - Hansen, Alvin H. (The Review of Economics and Statistics, 1946)
i. The notion seems to run through Terborgh's book 1 (and indeed in part through Wright's review) 2 that the economy3 thesis holds that economic stagnation is unavoidable. In fact, the bulk of my writing has been devoted to an analysis of economic policies which would give us an expanding economy and full employment. The question really is: Would a policy of mid-nineteenth-century laissez faire, now, give us that degree of expansion and full employment which we experienced in that century? 2. The essential issue is: Are the automatic forces making for investment outlets as strong in our world today as in the century preceding World War I? From the classicals on, (a) the discovery and development of new territory and new resources, (b) population growth, and (c) inventions, have always been recognized as leading factors underlying investment opportunities. In the century preceding World War I the existence of a vast unexploited continent with rich natural resources, together with the phenomenal growth of population, everywhere gave rise to optimistic expectations with respect to investment. Invention, new products, and new industries were equally important. Undeveloped resources and population growth may be described as extensive expansionist factors, while invention may be termed an intensive expansionist factor. No one denies that the extensive factors play in the current world a relatively smaller role. The argument of the critics seems to be: Well, why worry? -The intensive factors are still present. If one member of a team drops out the other can pull the full load. This may indeed be so, but at least the probabilities are the other way. I do not think that anyone will deny that if we should wake up tomorrow and find that a vast new rich continent had suddenly emerged in the Pacific or in the Atlantic, equal in resources to the North American continent, the investment opportunities for private capital in the next few decades would be enormously improved. 3. With respect to population growth, let anyone consider (as Goeffrey Crowther did in a recent article in Foreign Affairs) the probable volume of capital formation in the United States in the year 2000 compared with that in Great Britain. In making such an estimate, one would surely want to take cognizance of the larger probable growth of population in this country. That capital formation is related to volume of output is, so far as I know, not questioned. Nor is it questioned that increase in volume of output is related to: (a) growth of labor force and (b) increase in per capita productivity. The relation of capital formation (investment outlets) to population growth is now, it should be stressed, fully recognized by Terborgh in his new book. He argues that population growth has accounted for about one-third of capital formation. This figure is in fact somewhat higher than my 50-60 per cent of net capital formation.4 4. While admitting the major role of popu'George Terborgh, The Bogey of Economic Maturity (Chicago, Chemical and Allied Products Institute, I945). 2Pp. I8-22, below. 'The term secular stagnation, it should be noted, is not applicable alone to mature economies. It is perhaps the best English rendition of Spiethoff's phrase Stockung-Spanne. Even in the nineteenth century, we had prolonged periods of stagnation in which there was a preponderance of hard times, recovery and prosperity being short-lived and depressions long and severe. (See Fiscal Policy and Business Cycles, Chapter I.) 4 Terborgh is in doubt whether I meant gross or net, though the context and the language used by me should have made that quite clear. No one else as far as I know has assumed that I meant gross. I do use the term new investment, but I am not aware that the word total has ever meant gross. I used total because I was analyzing two component parts of net investment: (a) that related to population growth and the development of new territory and (b) that related to invention and technological progress.